2007
DOI: 10.1090/s0002-9939-07-09168-x
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of the Kontsevich-Vishik trace

Abstract: Let M be a closed manifold. We show that the Kontsevich-Vishik trace, which is defined on the set of all classical pseudodifferential operators on M , whose (complex) order is not an integer greater than or equal to − dim M , is the unique functional which (i) is linear on its domain, (ii) has the trace property and (iii) coincides with the L 2 -operator trace on trace class operators.Also the extension to even-even pseudodifferential operators of arbitrary integer order on odd-dimensional manifolds and to eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…This trace is called the generalized Kontsevich-Vishik trace (the original Kontsevich-Vishik trace is the special case of A 0 being a classical pseudo-differential operator) and given by By construction, the generalized Kontsevich-Vishik trace coincides with tr on trace-class operators. Furthermore, it was shown that the Kontsevich-Vishik trace is the only trace on the algebra of classical pseudo-differential operators that restricts to tr in L(L 2 (X)) [21]. These properties make the generalized Kontsevich-Vishik trace a prime candidate for path integral regularization as such a path integral regularization is consistent with respect to discretization (turning operators into matrices and, thus, trace-class) and Wick rotations (turning the path integral into pseudo-differential operator traces).…”
Section: Resultsmentioning
confidence: 99%
“…This trace is called the generalized Kontsevich-Vishik trace (the original Kontsevich-Vishik trace is the special case of A 0 being a classical pseudo-differential operator) and given by By construction, the generalized Kontsevich-Vishik trace coincides with tr on trace-class operators. Furthermore, it was shown that the Kontsevich-Vishik trace is the only trace on the algebra of classical pseudo-differential operators that restricts to tr in L(L 2 (X)) [21]. These properties make the generalized Kontsevich-Vishik trace a prime candidate for path integral regularization as such a path integral regularization is consistent with respect to discretization (turning operators into matrices and, thus, trace-class) and Wick rotations (turning the path integral into pseudo-differential operator traces).…”
Section: Resultsmentioning
confidence: 99%
“…When combined with Proposition 4.2, Theorem 3.3 gives the existence and the uniqueness of (Res k ) k∈N on L. [11] Uniqueness of traces 181 APPLICATION 4.4. When we combine Proposition 4.2 with the result of [9], the uniqueness of TR on odd-class classical PDOs for odd-dimensional manifolds and Theorem 3.5, we obtain a proof of the uniqueness of TR on L odd in odd dimensions.…”
Section: Then the Operatormentioning
confidence: 93%
“…2 [9] Uniqueness of traces 179 REMARK 3.6. If τ 0 = 0, then any graded trace or ordinary trace extending τ 0 on A vanishes.…”
Section: Proof We Proceed By Induction On Kmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1.4 An odd-class symbol as a sum of derivatives Proposition 1 (see Lemma 1.3 in [4], and [14]). Let n ∈ Z be odd.…”
Section: The Noncommutative Residue On Symbolsmentioning
confidence: 99%